LITERATUR REVIEW: PENGGUNAAN GAME ONLINE SEBAGAI STRATEGI KOPING DESTRUKTIF DI MASA PANDEMI COVID-19 - Azizah Heru, Maulidiyah Junnatul (Jurnal Keperawatan Profesional, 2023)
As the internet age is growing rapidly, one of the benefits of the development of the internet is for entertainment facilities, for example to play online games. Online games are an audio and visual based game that is played over the internet network.  Objective : To find out if the use of online games during the COVID-19 Pandemic is a destructive coping state. Methods : The source of the article used is through a database search google scholar, science direct and elsiver. Article searches are restricted from 2016 to 2021. The keywords used in the article searches are "online gaming", "internet gaming addiction" and "COVID-19 pandemic". This Literature Review uses 15 articles that fit the inclusion criteria. Results: Online gaming or online games from reviewed research greatly have a negative impact on online gaming users, because not always online games are useful and pose a lot of risks. Conclusion: The use of online games during the COVID-19 pandemic is a destructive coping strategy because the use of online games is not always beneficial and can pose many risks that negatively impact excessive gaming such as endangering mental health, sleep patterns, or physical health